An Exploration of the Growth Strategies of Small and Medium Technology Start-Up Companies in China - Cai, Jiaqi (2020)
This study aimed to explore the growth strategies used by small and medium sized technology start-up companies in China to acquire customers. This was to determine how Chinese technology start-ups identify customer acquisition strategies and the ways in which they apply them to their business. A qualitative interpretivist approach was undertaken, which encompassed conducting semi-structured in-depth telephone interviews on six owners and senior managers of small and medium sized technology start-ups based in China.